Structural control on fluid circulation in a graben system: Constraints from the Saint Pierre Bois quarry (Vosges, France). (May 2021) - Dezayes, Chrystel; Lerouge, Catherine; Innocent, Christophe; Lach, Philippe
Abstract: Defining the fracture network and the active fluid pathways are fundamental to characterizing a fractured reservoir. With this goal, we chose the Saint Pierre Bois quarry (Vosges Massif, France) as a natural analogue for the Permian-Stephanian cover (arkoses)/Hercynian basement (granite) transition that serve as geothermal reservoirs, for example at Rittershoffen, Landau and Insheim, where geothermal plants exploit this kind of reservoir within the Upper Rhine Graben (URG). During our study, along walls of the quarry, we measured fracture orientation on multiple 1D scanlines, sampled fracture fills and associated wall rock, and measured porosity. Our interpretation of the fracture dataset and associated mineral deposits and alteration indicates a large unmapped fault zone (displacement around 10m) we infer to cross the quarry. This fracture zone comprises a core zone (>50 m thick), which is the most highly altered-fractured zone in the quarry. In the transition zone (20–25m thick), some E-W faults cross and displace the arkose/granite transition. The two major fracture sets (E-W and NNE-SSW strikes) are present in the damage zone (>100m thickness) and are typically randomly distributed, but sometimes are grouped in clusters (defined by high spacing coefficient of variation). The E-W fractures and faults are the result of local tectonic inheritance in relation to the Villé basin formation at the end of the Hercynian orogen. Based on rock alteration, these structures constitute good pathways for fluid, first of all for the meteoric fluid during the E-W fault zone creation associated to the Villé basin opening, and then for the hot brine, which clogged the system by quartz precipitation during the burial of the basin.